Post-exercise Endothelium-Dependent Vasodilation Is Dependent on Training Status; Frontiers in Physiology; Vol. 11 - Kapilevich L. V. Leonid Vladimirovich; Kologrivova V. V. Valeriya Viktorovna; Zakharova A. N. Anna; Mourot L. Laurent (2020, 2020)
Title screen